Faro Waste Rock Project: Characterizing Variably Saturated Flow Behavior Through Full‐Scale Waste‐Rock Dumps in the Continental Subarctic Region of Northern Canada Using Field Measurements and Stable Isotopes of Water. Issue 3 (20th March 2020) - Bao, Zhongwen; Blowes, David W.; Ptacek, Carol J.; Bain, Jeff; Holland, Steven P.; Wilson, David; Wilson, Ward; MacKenzie, Peter
Abstract: Understanding water flow through variably saturated waste‐rock dumps is important for determining the extent of sulfide‐mineral oxidation, contaminant loadings, and impacts of waste‐rock effluent on groundwater and surface‐water quality. To better understand water flow within full‐scale waste‐rock dumps in the continental subarctic region of Northern Canada, a field experiment was undertaken at the Main and Intermediate Dumps at the Faro Mine Complex, Yukon Territory. Here we present results from an investigation of the hydrological behavior and quantification of the factors controlling water flow through unsaturated waste‐rock dumps and the impacts on long‐term drainage water quality. The results suggest that flow through the fine matrix materials was the dominant flow mechanism, with possible preferential flow through macropores and ponding/runoff during intense infiltration events (i.e., snowmelt and intense rainfall). Cross δ 18 O‐δ 2 H plots of pore water collected from near‐surface waste‐rock samples suggested that evaporation at the surface of the dumps occurred during precipitation‐free periods in the summer. Depth profiles of δ 18 O and δ 2 H of pore water extracted from core samples provided indications of internal evaporation within the waste‐rock dumps and pore‐water displacement mainly in response to summer rainfall events (rather than snowmelt). Mixing calculations using δ 18 O and δ 2 H show that 76–95% of pore water present in the waste‐rock matrix was derived from summer rainfall, leading to lower concentrations of dissolved constituents in the summer effluent, and vice versa in winter. The results will inform cover design and remediation options for the waste‐rock dumps at the Faro Mine Complex. Key Points: We reported the first measurements of δ 18 O and δ 2 H at the Faro Mine Complex (FMC), Yukon Territory Surface and internal evaporation occurred in the waste‐rock dumps We found summer rainfall- and evaporation-dominated pore-water displacement in the waste-rock dumps